Pengetahuan tentang Infeksi Menular Seksual dengan Perilaku Seksual Tidak Aman pada Remaja Putri Maluku Tenggara Barat di Daerah Istimewa Yogyakarta - Kora, Firmina Th; Dasuki, Djaswadi; Ismail, Djauhar (JURNAL KESEHATAN REPRODUKSI, 2016)
Background: Based on the Indonesian Demographic and Health Survey (IDHS, 2012), adolescents’ knowledge (females aged 15-24 years) about STI (Sexually Transmitted Disease) is still low under 50%. A total of 16.46% Indonesian adolescents have had sex, 46.26% of them have been doing it actively, first sex occurred in below 20 years of age.Objective: To determine the relationship between knowledge about sexually transmitted infections with unsafe sexual behavior.Method: This study is a quantitative and qualitative with cross-sectional study design. Subjects in this study were all female adolescents of West Southeast Moluccas who are continuing education in Yogyakarta. Univariable and bivariable data analysis was conducted using chi-square test statistic. Multivariable analysis was conducted using logistic regression to estimate the effective model.Result and Discussion: Low knowledge STI is practically and statistically related to unsafe sexual behavior with a p-value <0.05, RP 1.71 and CI 1.07 to 2.70. Low knowledge about STIs in adolescents increase the risk by 1.7 times for unsafe sexual behavior. Conclusion: 67,1% female adolescent who have unsafe sexual behavior. Female adolescents who have knowledge about STIs low 65.7%. Low knowledge STI significantly increases unsafe sexual behavior in adolescent girls. Unsafe sexual behavior conducted by adolescent female are sexual intercourse before the age of 20 not using condoms during sexual intercourse, and multiple sexual partner.Keywords: Knowledge of Sexually Transmitted Infections, Unsafe Sexual Behavior, Female Adolescent